Resurgence of ESG investments in India: Toward a sustainable economy - Gopal K. Sarangi (Asian Development Bank Institute (ADBI), 2021)
ESG investments have attracted wider attention from both investors and customers worldwide. These investments largely follow a triple-bottom-line approach that combines financial returns with environmental and social norms. The study in this context carries out a detailed assessment of the ESG development and evolution trajectory in India, maps the legal and regulatory landscape governing ESG investments, and conducts a sustainability evaluation of a set of corporate entities. It uses a mixed-method approach for its assessment. The findings suggest that ESG integrated assets have outperformed their counterparts. In addition, it emerges from the analysis that companies have performed relatively better in policy disclosure and governance parameters of ESG integration than in environmental and social factors. The mapping of ESG policies and regulations reveals that there has been a gradual widening of scope of ESG policies and that the ESG policy environment is moving away from a voluntary regime to a mandatory one. Finally, the sustainability assessment of a select set of corporate entities indicates that, in terms of both ambitions and practices, they place disproportionate emphasis on environmental aspects of sustainability and neglect social dimensions, both in their declarations and in their implementations.
Keywords: M14; Q56; Q01; 330; ESG investments; ESG policies and regulation; sustainability assessment ofcorporate entities; India